2017
DOI: 10.1021/acs.energyfuels.6b03228
|View full text |Cite
|
Sign up to set email alerts
|

Study on Deposits Containing Rich Fluorine, Boron, and Ammonium on the Heating Surface of a Flue Gas Cooler in a 300 MW Coal-Fired Boiler

Abstract: To understand deposit formation in the flue gas cooler, which is used to recover the exhaust heat from a 300 MW coal-fired boiler in China, a mineralogical study was carried out. Several deposit samples on the surface of the flue gas cooler were collected. Then, the samples were examined by X-ray fluorescence (XRF), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and energy-dispersive spectrometry (EDS). Mineralogical analysis showed that the deposits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to Figure 4, the major compounds in the outer layer of samples were similar, including ferric oxide, silica, calcium sulfate and alumina; in addition SiO 2 , Al 2 O 3 , and CaSO 4 were indicative of the formation of ash particles in the flue gas [23].…”
Section: Methodsmentioning
confidence: 99%
“…According to Figure 4, the major compounds in the outer layer of samples were similar, including ferric oxide, silica, calcium sulfate and alumina; in addition SiO 2 , Al 2 O 3 , and CaSO 4 were indicative of the formation of ash particles in the flue gas [23].…”
Section: Methodsmentioning
confidence: 99%
“…The low‐temperature fouling on the metal heating surface will greatly reduce the heat transfer efficiency of boiler heat recovery equipment such as air preheaters, low‐pressure economizers, and flue gas coolers due to the presence of fouling thermal resistance 15–19 . Besides, it can result in metal corrosion, serious blockage of the flue gas flow channel, and so on 20 . In brief, the existence of low‐temperature fouling in the tail flue will result in lower boiler efficiency and lead to an adverse effect on the normal and safe operation of coal‐fired power station boilers 21 …”
Section: Introductionmentioning
confidence: 99%
“…Vuthaluru et al 25 provided valuable information on the air preheater deposits and mineralogy, indicating that the temperature was an important factor in the low‐temperature fouling. Ma et al 20 found that NH 4 BF 4 could also result in severe fouling in the flue gas cooler. Meanwhile, numerical methods have been used to study the fouling process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation